The functional organization of the lateral frontal cortex: conjecture or conjuncture in the electrophysiology literature? - Rushworth, M; M Owen, A (1998)
While the importance of the prefrontal cortex for `higher-order' cognitive functions is largely undisputed, no consensus has been reached regarding the fractionation of functions within this region. Since Fuster and Alexander's first description of `working memory cells' the field has continued to be driven by electrophysiological recording studies, the results of which have provided the impetus for an abundance of studies using alternative methodologies, most notably, functional neuroimaging. However, even within the electrophysiological literature, there is considerable disagreement about how the functions of different prefrontal regions might best be described, a consideration that has implications for the interpretation of related studies in human subjects. In this article, we review the electrophysiological evidence for functional segregation within the frontal cortex in the context of related data from primate lesion studies and functional neuroimaging in humans, and attempt to reconcile the key findings with emerging cognitive models of lateral frontal lobe organization.